The Impact of Business Incubators on Entrepreneurship Performance: A Benchmark Study Based on Panel Models of Entrepreneurs in Middle Eastern Countries for the Period (2017-2023) - lilia, Sellam; Khaled , Ahmima (Journal of Ecohumanism, 2025)
Entrepreneurship has recently an active role in promoting economic activity in all contemporary economies, but it faces many obstacles that could lead to failure. With notable developments in this field, new support and assistance mechanisms have been created, the most important of which are business incubators that encourage investment and thus achieve economic growth and development for the country. This research paper addresses the concept of entrepreneurship as well as business incubators and their role in supporting the national economy and achieving local development.